2013
DOI: 10.3390/polym5010112
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Aliphatic Polypeptoids

Abstract: A series of polypeptoid homopolymers bearing short (C 1 -C 5 ) side chains of degrees of polymerization of 10-100 are studied with respect to thermal stability, glass transition and melting points. Thermogravimetric analysis of polypeptoids suggests stability to >200 °C. The study of the glass transition temperatures by differential scanning calorimetry revealed two dependencies. On the one hand an extension of the side chain by constant degree of polymerization decrease the glass transition temperatures (T g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 40 publications
9
72
1
Order By: Relevance
“…In recent years, the substrate scope for polymerization studies was further expanded to include a variety of R-NCA monomers bearing various N-substituents ( Figure 2). [5,6,[15][16][17][18][19][20][21][22] Luxenhofer et al demonstrated that the polymerizations of Me-NCAs using benzyl amine initiators were shown to proceed in a controlled manner without chain transfer or termination events, producing polysarcosines with narrow Poisson distribution (PDI < 1.1-1.3) and M n s that can be controlled by the initial monomer to initiator feed ratios. [56] The molecular distribution remains narrow (PDI 5 1.01-1.07) even after ten sequential polymerizations of Me-NCA monomers (DP < 100), attesting to the robustness of the living polymerization and suggesting the potential uses of the methods towards the synthesis of well-defined block copolypeptoids via sequential monomer addition.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, the substrate scope for polymerization studies was further expanded to include a variety of R-NCA monomers bearing various N-substituents ( Figure 2). [5,6,[15][16][17][18][19][20][21][22] Luxenhofer et al demonstrated that the polymerizations of Me-NCAs using benzyl amine initiators were shown to proceed in a controlled manner without chain transfer or termination events, producing polysarcosines with narrow Poisson distribution (PDI < 1.1-1.3) and M n s that can be controlled by the initial monomer to initiator feed ratios. [56] The molecular distribution remains narrow (PDI 5 1.01-1.07) even after ten sequential polymerizations of Me-NCA monomers (DP < 100), attesting to the robustness of the living polymerization and suggesting the potential uses of the methods towards the synthesis of well-defined block copolypeptoids via sequential monomer addition.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
“…[20][21][22]24] Polypeptoids with linear aliphatic N-substituents shorter than 2 carbons are amorphous, whereas polymers with longer linear aliphatic N-substituents (n 5 3, 4, 5, 6, 8, 10, 12, and 14) tend to be highly crystalline and pack into SCHEME 9 Postpolymerization functionalization of polypeptoids SCHEME 10 Synthesis of a library of cationic polypeptoids bearing different cationic amino groups (P1-P4), backbone chain lengths (DPs) (P4-P7), hydrophobic linker lengths (P4, P8, P9, and P10) and incorporation of hydrophobic N-substituents (P11). [78] Adapted with permission from the American Chemical Society lamellar structure in the solid state ( Figure 9A).…”
Section: Thermal Properties Of Polypeptoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…mp = 100.9 °C (5 °C min −1 ), 1 Sarcosine-N-Carboxyanhydride : The synthesis of sarcosine NCA was adapted from literature and modifi ed. [ 31 ] Sarcosine (15.16 g, 170.2 mmol, 1 eq) was weighed into a predried three-neck round-bottomed fl ask and dried in vacuo for 1 h. 300 mL of abs. THF were added under a steady fl ow of nitrogen and diphosgene (16.26 mL, 134 mmol, 0.8 eq) was added slowly via syringe.…”
Section: Monomer Synthesis (γ-Tert-butyl-l -Glutamate-n-carboxyan-mentioning
confidence: 99%